2016
DOI: 10.1002/adfm.201504998
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biological Functions of ZIF‐NP as a Delivery Vehicle: High Pulmonary Accumulation, Favorable Biocompatibility, and Improved Therapeutic Outcome

Abstract: Though zeolitic imidazole framework (ZIF) emerges as an advanced functional material for small-molecule delivery due to its unique features such as high loading and pH-sensitive degradation, there are extreme short of knowledge regarding its biological functions. To qualify this category of delivery vehicle, ZIF-8 nanoparticles (ZIF-NPs) with or without cargo are engineered and comprehensively investigated in vitro and in vivo. Interestingly, ZIF-NPs demonstrate strong bioadhesion but with limited internalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
80
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(88 citation statements)
references
References 68 publications
6
80
0
1
Order By: Relevance
“…[55] Figure 4f displays that the internalization was almost inhibited when the cells were cultured at 4 °C, indicating an energy-dependent-endocytosis process. It has been reported that the drug endocytosis process is mainly through the following three types of passway: a) macropinocytosis, b) caveolae-mediated endocytosis, and c) clathrinmediated endocytosis.…”
mentioning
confidence: 97%
“…[55] Figure 4f displays that the internalization was almost inhibited when the cells were cultured at 4 °C, indicating an energy-dependent-endocytosis process. It has been reported that the drug endocytosis process is mainly through the following three types of passway: a) macropinocytosis, b) caveolae-mediated endocytosis, and c) clathrinmediated endocytosis.…”
mentioning
confidence: 97%
“…47,48 Nonetheless, emerging evidence also suggests that the nanomaterials themselves could be refined for specific tissue accumulation and thus targeting through either a passive or active mechanism. 49,50 GO materials were uncovered to preferentially localize in the lung upon in vivo administration, [9][10][11][12] pointing out the rationale of using GO for lung targeting. To this end, we synthesized the MoS 2 /GO nanocomposites for the purpose of lung targeting.…”
Section: Preferential Lung Accumulation Of Mos 2 /Go Nanocompositesmentioning
confidence: 99%
“…41,42 Generally, caveolar, CME, and macropinocytosis are responsible for the internalization of particles of different sizes. 43,44 The pathway studies demonstrated that the endocytosis of SWCNHox may be mediated via multiple mechanisms.…”
mentioning
confidence: 99%